Recent Progress of Novel Nanotechnology Challenging the Multidrug Resistance of Cancer - Zhang, Chengyuan; Zhou, Xuemei; Zhang, Hanyi; Han, Xuanliang; Li, Baijun; Yang, Ran; Zhou, Xing (Frontiers in Pharmacology, 2022)
Multidrug resistance (MDR) of tumors is one of the clinical direct reasons for chemotherapy failure. MDR directly leads to tumor recurrence and metastasis, with extremely grievous mortality. Engineering a novel nano-delivery system for the treatment of MDR tumors has become an important part of nanotechnology. Herein, this review will take those different mechanisms of MDR as the classification standards and systematically summarize the advances in nanotechnology targeting different mechanisms of MDR in recent years. However, it still needs to be seriously considered that there are still some thorny problems in the application of the nano-delivery system against MDR tumors, including the excessive utilization of carrier materials, low drug-loading capacity, relatively narrow targeting mechanism, and so on. It is hoped that through the continuous development of nanotechnology, nano-delivery systems with more universal uses and a simpler preparation process can be obtained, for achieving the goal of defeating cancer MDR and accelerating clinical transformation.